Design and analysis of a Sub-6 GHz antenna array with high gain for 5G mobile phone applications - Bellekhiri, Abderrahim; Chahboun, Noha; Zbitou, Jamal; Oukaira, Aziz; Laaziz, Yassin (International Journal of Electrical and Computer Engineering (IJECE), 2024)
In this paper, we designed, analyzed, and simulated a 32-element antenna array for the sub-6 GHz band. Each radiating element is a square patch on a Rogers RT5880 substrate, featuring a relative dielectric permittivity of 2.2, a low-loss tangent of 0.0009, and a thickness of 0.508 mm, measuring 28.1×28.1 mm². Simulations were conducted using two electromagnetic solvers, advanced design system (ADS) and CST Microwave Studio, providing a comprehensive comparison of the results. To achieve a high balance between performance and antenna size, two 4×8 array antenna structures were designed. The simulations demonstrated excellent input impedance matching around 3.5 GHz for both configurations, with high gains of 20.5 dBi for the first and 18 dBi for the second configuration, along with directional radiation patterns. The dimensions were 315×576×0.578 mm³ for the first configuration and 170×961×0.578 mm³ for the second. These performance metrics make the proposed antenna arrays highly suitable for wireless communication technologies operating below 6 GHz, particularly for 5G mobile communications.